Role of endoscopic ultrasonography in staging of esophageal carnicoma - Uğur YILMAZ; Ahmet TEZEL; Ülkü SARITAŞ; Bülent YILDIRIM; Senem KÜÇÜKBAŞ; Gülay TEMUÇİN (Turkish Journal of Gastroenterology, 2020)
-